Abortion in Nepal: perspectives of a cross-section of sexual and reproductive health and rights professionals - Claire Rogers; Sabitri Sapkota; Anita Tako; Jaya A. R. Dantas (BMC, 2019)
Abstract Background Globally, women face many barriers in the attainment of sexual and reproductive health and rights (SRHR). Since 2002, the legalisation of abortion in Nepal has seen significant progress in the expansion of safe abortion and family planning services. Methods This qualitative, exploratory study was conducted in 2014 and uses nine in-depth, open-ended interviews with a cross-section of SRHR professionals, to explore their perspectives on abortion in Nepal. The study was underpinned by the Assets Focused Rapid Participatory Appraisal (AFRPA) research methodology and used the health information pyramid conceptual framework. Results Thematic content analysis revealed emerging themes relating to barriers to access and uptake of skilled safe abortion services and post-abortion family planning. Findings also emphasised current practical and legal components relating to the provision of medical abortion through pharmacies and highlighted issues of sex-selective abortion within the predominantly patriarchal society. Conclusion Effective and ongoing sector-wide monitoring and evaluation of safe abortion services and their staff is essential for women in Nepal to have adequate access to effective and efficient safe abortion services, access to contraception and sexual and reproductive health (SRH) information post-abortion and to ensure adherence to current Safe Abortion Policy. It is critical that the unsafe (less and least safe) provision of medical abortion through pharmacies and sex-selective abortion continues to be investigated and that innovative strategies are formulated to ensure the cultural, reproductive and sexual health and rights of Nepali women are realised.